Demanda por seguro de automóvel no Rio de Janeiro - Freitas, Cristiana Caldeira Garcia de (2018)
This thesis aims to estimate the demand for auto insurance in the city of Rio de Janeiro. Due to the availability of consumer level data, a brief review of discrete choice models was made, focusing on Logit with random coefficients. In order to effectively implement the models, we had to deal with a peculiarity of the insurance industry: prices vary according to each individual. As we only have the effective prices of the contracted policy, a random forest model was tested to generate expected premium values for the insurers.